Pengaruh Interval Training Terhadap Peningkatan Daya Tahan Kardiovaskular pada Ekstrakurikuler Futsal Tingkat SMP - Malau, Billy Desmawan; Mahfud, Imam (Jurnal Porkes, 2025)
The purpose of this study was to determine the effect of interval training on cardiovascular endurance in students who take part in extracurricular futsal. The research used quantitative methods. This study used an experimental approach with a one group pretest-posttest design. The population in this study consisted of 18 students in the futsal extracurricular program and used total sampling, which involved all members of the population as samples. The instrument used in this research is the beep test. The data analysis technique used in this study was the paired sample t-test. The t test results show a significance value of 0.000 (< 0.05), so the alternative hypothesis is accepted, pretest data shows the highest value of 39.5, the lowest value of 26.8, the average pretest score of 31.98 increased to 37.16. sig. 2-tailed with a significance value of 0.000 < 0.05, the results of the analysis indicate a significant difference in pretest and posttest data after treatment. Therefore, it can be said that interval training has a positive impact on increasing the cardiovascular endurance of futsal extracurricular students at the junior high school level.